Electrogenerated Chemiluminescence of Cationic Triangulene Dyes: Crucial Influence of the Core Heteroatoms. Issue 52 (5th November 2015) - Adam, Catherine; Wallabregue, Antoine; Li, Haidong; Gouin, Jérôme; Vanel, Rémi; Grass, Stéphane; Bosson, Johann; Bouffier, Laurent; Lacour, Jérôme; Sojic, Neso
Abstract: Trianguleniums are fascinating conjugated hexacyclic cations that exhibit interesting electronic and optical properties. Herein, the electrogenerated chemiluminescence (ECL) emission of this family of fluorescent dyes is reported for the first time. Redox behavior and fluorescence properties of eight cationic triangulene luminophores with different heteroatom patterns in the core structure and various pending substituents were examined to rationalize the ECL. Clearly, the more electron‐rich the carbocation, the more efficient the corresponding ECL; two very distinct classes of triangulenes can be drawn from these studies by using an ECL wall sufficiency formalism. Abstract : Electrochemiluminescence : Electrogenerated chemiluminescence (ECL) of cationic triangulene dyes is reported here for the first time. The nature of the heteroatoms in the core structure strongly influences the ECL capability (see figure). Triaza‐ and diazatriangulenium (TATA + and DAOTA + ) exhibit strong ECL, unlike dioxa‐ and trioxatriangulenium (ADOTA + and TOTA + ), which is rationalized by the electrochemical and photochemical properties of the dyes.